Certain Rheological Aspects of Functionalized Guar Gum. (24th April 2013) - Kapoor, Meenu; Khandal, Dhriti; Gupta, Ruchi; Arora, Pinklesh; Seshadri, Geetha; Aggarwal, Saroj; Khandal, Rakesh Kumar
Abstract : Guar gum and its derivatives are highly important industrial hydrocolloids as they find applications in various industrial sectors. Guar is a polymer of high molecular weight and its aqueous solutions exhibit unique rheological properties, which has led to its wide acceptance by the industry. In certain industrial applications low molecular weight guar and its derivatives are needed, and conventionally chemical depolymerisation of guar is carried out for this purpose. Radiation processing is a novel and green technology for carrying out depolymerization and can be an ideal substitute for chemical depolymerisation technique. In order to study the effect of radiation on guar derivatives, three types of derivatives have been taken in the present study: carboxymethyl, hydroxyethyl, and methyl guar. The effect of 1–50 KGy radiation dose on the rheological behavior of these derivatives has been studied, and the results have been described in the present paper. The effect on storage and loss modulus with respect to frequency and effect on viscosity with respect to shear rate have been discussed in detail.